Efektivitas Teknik Role Play dalam Membantu Mengurangi Perilaku Agresif - Taufik Hidayah Suhada Putra; Khairul Bariyyah; Devi Permatasari (Universitas Kanjuruhan Malang, 2020)
Aggressive behavior is an act or abusive behavior used in socializing or communicating in a society that does not conform to the norm in masayarakat, and can harm others. One of the deviant behaviors that often arise among teenagers is that it is less able to control their emotions, and it is easy to express displeasure through inappropriate words. Group guidance helps individuals find themselves, direct themselves, and can adjust to their surroundings. This research aims to test the effectiveness of role play techniques to reduce the aggressive behavior of grade VIII students at Sunan Ampel Performance Junior High School. The research method used is experimental research with one group pretest posttest design type. Research sample of 10 students selected with Cluster Random Sampling technique. Research instruments use thescale of study, expert test and aggressive behavior scale, data analyzed with technologyk validitytest, realibiltas, before after design. The results showed students' aggressive behavior decreased after participating in group mentoring activities with role play techniques or effective role play techniques to reduce students' aggressive behavior. The nextresearcher's advice b agi,time should be effective when providing services to students so as not to interfere with the schedule of students who participate in extra activities in school